THE EFFECT OF USING WORDLESS PICTURE BOOK ON STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT - Sirikit Karola Br Sembiring; Johan Sinulingga (Universitas Negeri Medan, 2016)
This study was conducted as an attempt to discover the effect of Using Wordless Picture Book on students’ achievement in writing recount text. It was an experimental research. The subject was students of Grade VIII, SMP Negeri 1 Stabat. Two classes from five parallel classes were taken by lottery technique which divided into two groups, 30 students as control group and 30 students as experimental group. The instrument used in this research is to find quantitative data. The analysis in were showed that the scores of the students in the experimental group were significantly higher than the scores of the students in the control group at the level of significant  = 0.05 with the degree of freedom (df) 58, t-observed value 3.006 > t-table value > 2.000. The findings indicate that using Wordless Picture Book significantly affected the students’ writing achievement. So, English teachers are suggested to use Wordless Picture Book in order to improve students’ achievement in writing recount text.